2019
DOI: 10.1016/j.jnucmat.2019.151808
|View full text |Cite
|
Sign up to set email alerts
|

The influence of carbon impurities on the formation of loops in tungsten irradiated with self-ions

Abstract: The microstructure changes taking place in W under irradiation are governed by many factors, amongst which C impurities and their interactions with self-interstitial atoms (SIA). In this work, we specifically study this effect by conducting a dedicated 2-MeV self-ions irradiation experiment, at room temperature. Samples were irradiated up to 0.02, 0.15 and 1.2 dpa. Transmission electron microscopy (TEM) expectedly revealed a large density of SIA loops at all these doses. Surprisingly, however, the loop number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…(ii) Both single crystal and ITER specification tungsten exhibit the maximum irradiation hardening at Tirr=800 °C, which is consistent with the reported peak swelling at 800 °C [19]. The computational analysis using object kinetic Monte Carlo calculations [52][53][54] also supports this finding.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…(ii) Both single crystal and ITER specification tungsten exhibit the maximum irradiation hardening at Tirr=800 °C, which is consistent with the reported peak swelling at 800 °C [19]. The computational analysis using object kinetic Monte Carlo calculations [52][53][54] also supports this finding.…”
Section: Discussionsupporting
confidence: 83%
“…3, the maximum radiation hardening for the SC in the dose range of 0.6-1 dpa is observed at 800 °C, which is consistent with the reported peak swelling at 800 °C [19]. Recently, a similar trend with irradiation temperature was registered and discussed for the same material but irradiated only up to 0.12 dpa [20], where this finding was substantiated based on positron annihilation spectroscopy (PAS) data and complimentary object kinetic Monte Carlo (OKMC) calculations [52][53][54]. The maximum hardness was explained by the contribution coming from the high density of voids, while the reduction of the irradiation hardening above 800 °C was associated with decreasing a void number density as suggested by the OKMC simulations.…”
Section: Irradiation Induced Hardness In Set 1 Materialssupporting
confidence: 83%
“…Another important question to be addressed concerns the actual content of minor alloying impurities (such as carbon, oxygen, nitrogen) and their spatial distribution (i.e., dissolved or gathered by dislocations and grain boundaries). Indeed, some recent computational studies [61,62] suggest that the interaction of neutron irradiation defects with carbon must have important implications on the accumulation of the irradiation damage in W, at least in the irradiation temperature range 22-800 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Castin et al [21] demonstrated the influence of carbon on the formation of loops by using object kinetic Monte Carlo (OKMC) modeling and secondary ion mass spectroscopy (SIMS). Besides, first-principle calculations predicted that vacancy-type defects interact strongly with LEs.…”
Section: Introductionmentioning
confidence: 99%
“…The greater the number of carbon atoms n, the more the V-Cn complexes generated hinder the trapping of positrons. [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%